Optimal cut-off age for AJCC staging system in Middle Eastern differentiated thyroid cancer - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Qadri, Zeeshan; Annaiyappanaidu, Padmanaban; Siraj, Nabil; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Endocrinology, 2025)
BackgroundAge cut-off of 55 years has been included in the eighth edition of the American Joint Committee on Cancer (AJCC) TNM staging, since it led to better prediction of disease-specific survival (DSS) of patients with differentiated thyroid cancer (DTC). However, optimal age cut-off in DTC patients from Middle Eastern ethnicity has not been fully explored.MethodsWe retrospectively analyzed a large cohort of 1721 adult DTC patients. The optimal age cut-off value was determined using several age cut-offs (between 20 and 85 years) to assess DSS. Harrel’s C-Index, Akaike information criterion (AIC) and Bayesian Information Criterion (BIC) were used to assess statistical model performance of the TNM staging system (eighth edition), with different age cut-offs for prediction of DSS.ResultsThe median age of patients at diagnosis was 39.9 years (inter-quartile range 31.0 – 51.7 years) and 75.5% (1299/1721) were female. Median follow up was 9.3 years and 10 years DSS was 97.1%. For DTC overall, an age cut-off of 50 years had the best statistical model performance. On receiver operating characteristic curve analysis, the optimal age cut-off for prediction of DSS was 50.5 years (area under the curve = 0.872, p < 0.0001).ConclusionIn this large cohort of Middle Eastern DTC patients, an age cut-off of 50 years was more appropriate for TNM staging to achieve better predictability for DSS. Therefore, implementation of different age cut-off for DTC in Middle Eastern patients could improve the predictive value for TNM staging system, allowing for better therapeutic and surveillance approach for these patients.